1994
DOI: 10.1021/j100082a034
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electronic Properties of Graphite and Graphite Intercalation Compounds MC8 (M = K, Rb, Cs) Governing Their Scanning Tunneling Microscopy Images

Abstract: Several puzzling observations in the scanning tunneling miucroscopy (STM) and atomic force microscopy (AFM) studies of highly oriented pyrolytic graphite (HOPG) and its intercalation compounds MCg (M = K, Rb, Cs) were investigated on the basis of atom-atom potential and Coulombic interaction energy calculations. The charge or spin density wave state of a graphite monolayer is found inconsistent with an identical peak registry of the HOPG STM images obtained at plus and minus bias voltages. Simultaneous STM/AFM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 0 publications
4
40
0
Order By: Relevance
“…An asymmetry of STM images with respect to ␤ site carbons in graphite has been observed by several groups. 18,19 Whangbo et al 27 concluded from experimental work that this feature of STM images derived from both mechanic and electronic effects. Our findings of surface polarization and deformation induced by deposited particles support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…An asymmetry of STM images with respect to ␤ site carbons in graphite has been observed by several groups. 18,19 Whangbo et al 27 concluded from experimental work that this feature of STM images derived from both mechanic and electronic effects. Our findings of surface polarization and deformation induced by deposited particles support this theory.…”
Section: Discussionmentioning
confidence: 99%
“…A simple analysis would lead one to expect the opposite, because the ␣ sites have a direct neighbor underneath and thus should be harder. However, Whangbo et al (29) found that for large tip atoms such as tungsten, the ␤ sites appear to be harder. Fig.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5][6] The most common stoichiometry is C 8 K. [7] Although, initially, C 8 K was used as a catalyst in polymerization reactions, [8] and in the nuclear and side-chain alkylation of aromatic compounds by ethylene, [9] the use of C 8 K as a reducing agent has also been investigated. [10][11][12][13][14][15][16][17][18][19][20] The use of C 8 K as a metallation agent in the alkylation of nitriles, esters, [21] and oxazines, [22] and in the reductive cleavage of carbonsulfur bonds in vinylic and allylic sulfones has been reported.…”
mentioning
confidence: 99%